Rivalry between the Leading Powers in the Context of Global Interdependence - I. A. Istomin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The existence of parallel trends in development of current international system, that of growing controversies between the leading states, on the one hand, and increasing global economic interdependence, on the other, raises question about their possible interrelation. The paper examines the impact of close economic relations among major powers on their increased competition for positional advantages in the sphere of international regulation and institutional power. High relevance of this issue stems from the fact that integration of one’s national preferences in the regulatory structures provides country with a long-term influence and increases its international competitiveness. The author identifies key features of current relations between the world’s leading powers and demonstrates that the 2010s witnessed a reemergence of intense rivalry among great powers as the rise of alternative centers of power challenges international position of the United States. The paper proceeds with an examination of competing theoretical approaches to assessing stability of the current configuration of international system as well as to explaining the impact of economic interdependence on international conflict. The author emphasizes that the appeal to economic interdependence has become one of the main lines of argumentation in the Western expert community since the end of the 2000s in terms of justifying prospects for a peaceful and relatively conflict-free evolution of the world order. However, international developments in the late 2000s-2010s show that the sphere of institutional regulation of global economy is rapidly becoming one of key areas of competition between the leading powers. The paper also examines certain social and technological trends that can limit a further growth of global economic interdependence. The current situation turns out to be the ‘worst of possible worlds’, in which the growing states’ needs for access to world markets are compounded by significant variations in their competitive advantages, and resulting differences in their preferences regarding the evolution of international economic regulation. The conclusion is drawn that such combination entails risks of a further aggravation of contradictions between the major international players.